STRATEGI PENANGANAN ANAK ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) DI TK: STUDI OBSERVASI DI KB-TK AMANAH - Eliana Dewi; Yahdinil Firda Nadhirah (STKIP Subang, 2026)
This study aims to describe the strategies of teachers in handling children with ADHD in kindergartens (TK), especially in KB-TK Amanah West Jakarta. The research method uses a descriptive qualitative approach with observation and interview techniques on teachers and principals. The results showed that effective strategies in handling children with ADHD include the use of visual schedules, personal instructions, reward systems, and quiet spaces. Collaboration between teachers, psychologists, and parents is key to success in supporting child development. This study confirms the importance of a holistic approach and an inclusive environment to help children with ADHD develop optimally at school